Calculation of Energy Interaction Parameters for the Complexation of Pr(III) and Nd(III) with 1,10-Phenanthroline and 2,2'-Bipyridyl by 4ƒ-4ƒ Absorption Spectral Analysis - YAIPHABA, N.; DAVID SINGH, TH.; INDIRA DEVI, M.; RAJMUHON SINGH, N. (Asian Journal of Chemistry, 2010)
Absorption difference and comparative absorption spectroscopic studies involving 4f-4f transitions on Pr(III) and Nd(III) with structurally related 1,10-phenanthroline and 2,2'- bipyridyl complexes in DMF, CH3CN, dioxane, CH3OH and their equimolar mixtures have been carried out. Variations in the spectral energy parameters like Slator Condon (FK), Lande spin orbit coupling (ξ4f), nephelauxetic ratio (β) and bonding parameter (b½) and per cent covalency (δ) are calculated and correlated with the interaction of Pr(III) and Nd(III) with 1,10- phenanthroline and 2,2'-bipyridyl. The marginal decrease in the values of FK and ξ4f are correlated with the increase in the value of β. The difference in the energy parameters with respect to donor atoms and solvents reveal that the chemical environment around the lanthanide ion has great impact on f-f transition and any change in the environment results in modifications of the spectra.